Food preparation tool: designing for the visually impaired / Nurul Shafinaz Ibrahim - Ibrahim, Nurul Shafinaz (2013)
This writing paper describes and discussed about handicap product for visually impaired person. Handicap people require a product which incorporates disability or imparity of themselves. Products which were designed and market for the disable are broad, so it is important to consider quality product for the disabled people. Users (visually impaired) are considered significant users as they cannot see like the normal people. This target group of people come with lower quality jobs; higher unemployment, lower income, and lower social status are not accessible to many of the products and services provided at the market. The topic for this report writing is Food Preparation Tool: Designing for The Visually Impaired. The keywords of this topic divided into four like, Disabled People, Visually Impaired, Blindness, and Kitchen Utensils. The researcher will explain more in depth these keywords in this report writing. The main problem and issue regarding this topic is the visually impaired facing with the difficulties kitchen activities especially when they want to frying the food. All of the household activities they can manage properly but when they at the kitchen they face with the dangerous while they are doing the cooking activity. So, the purpose of this study is to design the product for visually impaired based on their problems and needs and at the same time can protect them from getting any dangerous while cooking at the kitchen.